Ketahanan Pangan dengan Kejadian Stunting Pada Balita di Masa Pandemi Covid-19 - Nafilah, Nafilah (NUTRITURE JOURNAL; Vol 2 No 2 (2023): Nutriture JournalDO - 10.31290/nj.v2i2.3928, 2023)
Background : Stunting is a growth failure conditions in toddlers caused by chronic malnutrition so that children are too short for their age. The impact of stunting can inhibit brain development, not optimal body size, and metabolic disorders. Food security in the household can affect the lack of food intake for family members so that it can increase the incidence of stunting in toddlers. With the emergence of Covid19 in Indonesia, it will have an impact on household food security. Objective : This study aims to analyze the relationship between household food security and the incidence of stunting in toddlers during the Covid-19 pandemic . Method s : Respondents of this study were 65 toddlers aged 0-59 months in Klenggotan Hamlet. This observational research used a simple random sampling method. Food security data was obtained through the HFIAS (Household Food Insecurity Access Scale) questionnaire and categorized into 2, namely food security and food insecurity. Stunting incidence data obtained from anthropometric measurements were categorized into 2, namely stunting and not stunting. Results : The number of stunted toddlers is 11 toddlers (17%) and those who are not stunted (normal) are 54 toddlers (83%). There were 63% of family have the food insecure category. Food security was not related to the incidence of stunting in toddlers during the Covid-19 pandemic (OR= 3.094, 95% CI= 0.609 – 15.719, p= 0.191). Conclusion: Food security is not related to the incidence of stunting in toddlers during the Covid-19 pandemic.